(untitled) (Indian Journal of Animal Production and Management, 2024)
A study was conducted to identify the species of chicken in high heat processed chicken secondary by-product comprising of poultry blood meal. A total of 30 samples of poultry blood meal were collected from different poultry processing plants in Tamil Nadu. Species specific polymerase chain reaction was employed to validate the meat species identification in heat processed secondary poultry by-products. Custom designed primer sequences of mitochondrial cyt b gene were utilised for the present study. The results revealed successful amplification of chicken species at 227 base pairs in samples of all the blood meal samples. Thus, it was concluded that species specific polymerase chain reaction technique can be effectively used in the screening of chicken meat species in different heat processed secondary by-products for quick and reliable results.